Etilen Luka, Aktivitas Enzim Peroksidase, Polifenol Oksidase, dan Fenil Alanin Liasepada Irisan Mesokarp Labu Kuning - Murdijati Gardjito; Mochamad Adnan; Tranggono Tranggono (agriTECH, 2006)
Winter squash fruit is a non-climateric fruit which produced very low ethylene as intact fruit but peeled or sliced mesocarp produced a considerably high wound-ethylene. In certain level of concentration, ethylene could induce various reaction in the wound tissue. This study has objectives of obtaining informations on the influence of wound ethylene on the activities of peroxidase (POD), polyphenol oxidase (PPO), and phenyl alanine ammonia lyase (PAL) which catalyze some physiological process related with the changes in colour, flavour, and taste in the wound fruit tissue or its products. Experiments in this study were conducted in continous phase of 44 hours using flowlhrough system at 25 Â°C. Analysis and measuremets were done for ethylene, POD, PPO, and PAL enzymes at certain time interval. The sample used were disks of 9 mm in deameter and 2 mm thickness and cylinders of 14 mm in deameter and 2 cm in heihgt. The Results of this study indicated that the presence of wound combined with the certain level of wound ethylene formation induced the POD enzyme activity. The PPO activity increased proportionally with the increased surface area ratio to the fresh weight of wounded tissue. PAL activity was only evident 3 hours after wounding. The PAL activity increased following the same pattern of wound ethylene formation. The larger the woundsurface area ratio to the fresh weight of the tissue, the more ethylene were produced, and the higher the activities of those enzymes. Various pretreatments could effectively suppress the formation of wound ethylene and lowered activities of those enzymes.